Pengaruh Current Ratio, Debt To Equity Ratio, Gross Profit Margin, Total Assets Turnover Terhadap Pertumbuhan Laba Yang Dimoderasi Ukuran Perusahaan - Firli Dwi Lianingsih; Nur Ainiyah; Syaiful Bahri (CV. Kalimasada Group, 2025)
This study examines the impact of financial ratios on earnings growth in insurance companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024, considering company size as a moderator variable. This study analyzes four key ratios-Current Ratio (CR), Debt to Equity Ratio (DER), Gross Profit Margin (GPM), and Total Asset Turnover (TATO)-to evaluate their impact on earnings growth through the perspective of signal theory. Using quantitative methods, purposive sampling was used to select twelve insurance companies that consistently generated profits, resulting in sixty firm-year observations. Data were obtained from annual reports available on the official IDX website and analyzed through multiple linear regression and Moderate Regression Analysis (MRA). The results show that TATO has a large impact on earnings growth, but CR, DER, and GPM do not have a large impact. In addition, firm size strengthens the correlation between DER and TATO with earnings growth, while reducing the relationship between CR and earnings growth; firm size has no moderating effect on GPM. These results show how important asset efficiency is in generating profits in the insurance industry and that firm size has a major influence on its performance.